2019
DOI: 10.1103/physrevd.100.056011
|View full text |Cite
|
Sign up to set email alerts
|

Causality and dissipation in relativistic polarizable fluids

Abstract: We analyze the breakdown of causality for the perfect fluid limit in a medium with polarizeability. We show that to restore causality a relaxation term linking vorticity and polarization, analogous to the Israel-Stewart term linking viscous forces and gradients,is required. This term provides a minimum amount of dissipation a locally thermalized relativistic medium with polarizeability must have, independently of its underlying degrees of freedom. For ferromagnetic materials an infrared acausal mode remains, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 58 publications
(63 reference statements)
3
81
0
Order By: Relevance
“…Recent measurements of the Λ-hyperon spin polarization in heavy-ion collisions by the STAR experiment [1,2] have inspired a broad interest in the theoretical studies related to spin polarization and vorticity formation. The results of various investigations that refer to: the spin-orbit coupling [3,4,5,6,7], statistical properties of matter in global equilibrium [8,9,10,11,12,13], kinetic models of spin dynamics [14,15,16,17], hydrodynamics with triangle anomalies [18,19] and the Lagrangian formulation of hydrodynamics [20,21,22] have been reported in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements of the Λ-hyperon spin polarization in heavy-ion collisions by the STAR experiment [1,2] have inspired a broad interest in the theoretical studies related to spin polarization and vorticity formation. The results of various investigations that refer to: the spin-orbit coupling [3,4,5,6,7], statistical properties of matter in global equilibrium [8,9,10,11,12,13], kinetic models of spin dynamics [14,15,16,17], hydrodynamics with triangle anomalies [18,19] and the Lagrangian formulation of hydrodynamics [20,21,22] have been reported in this context.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, it would be interesting to explore in more detail the relation of the framework given in Ref. [5] to anomalous hydrodynamics [31,32] and the Lagrangian formulation of hydrodynamics [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, "ideal" relativistic hydrodynamics with spin was proposed in the context of the QGP [9] (See also Refs. [10][11][12] for recent attempts to apply a Lagrangian description of the spinful relativistic fluid), in which spin is regarded as a conserved quantity in the leading-order of a gradient expansion. However, the aforementioned nonrelativistic formulation has shown that spin is not conserved even at the leading order.…”
mentioning
confidence: 99%
“…Linear mode analysis.-Relativistic hydrodynamic equations with spin are obtained by plugging the constitutive relations (12) and (13) into the conservation laws (1). Below, we consider linear perturbations on top of global thermal equilibrium, and solve the hydrodynamic equations to discuss the dynamic evolution of the (non-)hydrodynamic modes in a spinful relativistic fluid.…”
mentioning
confidence: 99%